Joint expertise partnership talk with the National Water Services Commission (SPAN) / Salina Alias, Zuhaida Mohd Zaki and Amir Khomeiny Ruslan - Alias, Salina; Mohd Zaki, Zuhaida; Ruslan, Amir Khomeiny (Unit Penerbitan FKAPP, 2022)
UITM, Pulau Pinang - On December 12, 2023, Pusat Pengajian Kejuruteraan Awam, Universiti Teknologi MARA (UITM) Cawangan Pulau Pinang organized an Industry Professional Talk Program entitled "Perkongsian Kepakaran Bersama Suruhanjaya Perkhidmatan Air Negara (SPAN)." The talk aimed to provide insights into the management of water services in Malaysia and was organized by the lecturer of CEW555 "Water and Wastewater Infrastructural Design" course. The event, which took place in Bilik Perdana, was attended by 88 students and three lecturers from the Faculty of Civil Engineering. The keynote speaker for the talk was Ir. Ts. Mohd Zaidi Mohamad Saad, who is an expert in water management and currently working with SPAN. The talk covered a range of topics related to the management of water services in Malaysia, including the roles and functions of SPAN, the responsibilities of SPAN towards the public, the SPAN Act, and social responsibilities in water management. According to Rachel Anak Hyacinth, a student who attended the talk, "The program provided us with a valuable opportunity to learn about the management of water services in Malaysia. The talk was very informative and provided insights into the various challenges faced by SPAN in managing water services in the country." Normashita Binti Abdul Halim, another student who attended the talk, stated that "The program has piqued my interest in the field of water management, and I look forward to learning more about this topic in the future." To further enhance the engagement of students, the event also included a quiz, which was well-received by the participants. The organizers also gave out prizes to the students who answered the quiz questions correctly. Overall, the event was a success, providing students with a unique opportunity to learn from industry experts and gain insights into the management of water services in Malaysia. The organizers hope to continue organizing such events in the future to further enhance the knowledge and skills of the students in the field of civil engineering.